2016
DOI: 10.1186/s12884-016-0888-x
|View full text |Cite
|
Sign up to set email alerts
|

Boosting antenatal care attendance and number of hospital deliveries among pregnant women in rural communities: a community initiative in Ghana based on mobile phones applications and portable ultrasound scans

Abstract: BackgroundThe World Health Organization has recommended at least four antenatal care (ANC) visits and skilled attendants at birth. Most pregnant women in rural communities in low-income countries do not achieve the minimum recommended visits and deliver without skilled attendants. With the aim of increasing number of ANC visits, reducing home deliveries, and supplementing care given by ANC clinics, a proposed system based on low-cost mobile phones and portable ultrasound scan machines was piloted.MethodsA samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…Majority of the results were observational studies, with 7 prospective cohort studies, 3 cross‐sectional studies and 1 retrospective data analysis . Other study designs included a non‐blinded clustered randomised control trial, a pre‐post survey, a randomised control trial, a blinded investigational study, a field action report and a survey followed by a pilot project …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Majority of the results were observational studies, with 7 prospective cohort studies, 3 cross‐sectional studies and 1 retrospective data analysis . Other study designs included a non‐blinded clustered randomised control trial, a pre‐post survey, a randomised control trial, a blinded investigational study, a field action report and a survey followed by a pilot project …”
Section: Resultsmentioning
confidence: 99%
“…Africa was the region with the largest volume of literature, with 11 studies identified . Common themes explored included the utilisation of ANC, clinical knowledge and skills and patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction term, programme area*round of data collection, indicated the effect of the CoC in the context of the EPPICS standard activities. Covariates, including maternal age, education, parity, employment status, ethnicity, and distance from nearest health facility, were selected based on the literature (Ahmed et al 2010;Amoah et al 2016;Asundep et al 2013;Pell et al 2013;Simkhada et al 2008), and were included in all models. To examine the relationship between programme area and round of data collection, the interaction was plotted using the margins command in Stata 13.0.…”
Section: Methodsmentioning
confidence: 99%